From Mesopotamia to the Nebraska State Capitol: Assyrian Revival and new American meanings. (2020) - Miller, Eva
Abstract : Bertram Grosvenor Goodhue's influential 'prairie skyscraper' design for the Nebraska State Capitol, inaugurated in 1928, has long defied stylistic categorization. A now greatly overlooked element of its unclassifiable style was noted in numerous assessments at the time which identified 'Oriental', 'Assyrian' or 'Assyrian-Babylonian' features which, despite (or because of) their associations with a deep antiquity, contributed to the new, distinctly American architecture of the building, and of its sculptural programme by Lee Lawrie. This article considers the Assyrianizing tendencies of the capitol in the context of Art Deco interest in the 'revival' of ancient styles, and American civic architecture's engagement with the ancient Middle Eastern past as an origin of civilization. Goodhue's close collaboration with Lawrie, muralist Hildreth Meière, and 'symbologist' Hartley Burr Alexander exemplified the productive and creative application of revived ancient iconography, which was employed in Nebraska in the service of various historical narratives and as a reflection of the designers' aesthetic appreciation for Assyrian sculptures. Finally, this article also investigates how the capitol's treatment of the ancient Mesopotamian 'lawgiver' Hammurabi influenced 'Hammurabis' in subsequent sculptural contexts, including in the State Capitol of Louisiana, American federal government buildings, and the Oriental Institute of the University of Chicago.